The tourism and agro-tourism potential analysis in Tulcea county - Eugenia-Dorina Ciobanu (Rădoi); Raluca Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Tulcea County is a special tourist area, with a natural and anthropic touristic potential extremely rich and with real development opportunities in this area. An analysis of the touristic activity in the county can be particularly useful, so this work intends to analyze and present the touristic potential and the agrotourism potential of Tulcea County and the degree of use of it at this point. All these analyses will be made having in sight the elaboration and implementation of some potential effective strategies of development and recovery, at maximum range, in the touristic activity, also present and in the future.Through the development of touristic and agrotouristic pensions' activity carried out in this area, will be able to record the visible developments, economic and social developments in the County, leading to an increase in the standard of living of the inhabitants, especially those from rural areas, who are currently living at the edge of existence.
Keywords: Q01; Z3; O13; 330; agro-tourism; rural tourism; Tulcea Region; Romania